Record of fire residues and pollen from Lake Prespa and Lake Ohrid (SW Balkans) - Luisa Wöstehoff; Arne Kappenberg; Eva Lehndorff; Bernd Wagner; Konstantinos Panagiotopoulos; Wulf Amelung (PANGAEA, 2023)
The datasets include measurements of black carbon, microcharcoal, and pollen content in sediment samples from Lake Prespa and of black carbon content in sediment samples from Lake Ohrid. The data have been used to reconstruct past human-environment interactions in a region known for its extraordinary plant biodiversity and located on a possible dispersal route of anatomically modern humans from Africa. Lake Prespa core composite 1215 (40°57 extquotesingle50 extquotesingle extquotesingle N, 20°58 extquotesingle41 extquotesingle extquotesingle E) was collected at 14.5 m water depth in November 2009 and June 2011, comprises a total composite length of 17.76 m and covers a timespan of 92 ka (https://doi:10.1016/j.quaint.2012.05.048; https://doi:10.5194/cp-10-643-2014). A sediment succession of Lake Ohrid was recovered within the scope of the International Continental Scientific Drilling Program (ICDP; Wagner et al. 2019) at the DEEP site (Fig. 1; 41°02'57 extquotesingle extquotesingle N, 20°43'54 extquotesingle extquotesingleE, 243 m water depth; https://doi:10.5194/bg-13-1179-2016) in 2013. Black carbon has been analysed via benzene polycarboxylic acids (https://doi.org/10.1016/S0146-6380(98)00194-6; https://doi.org/10.1016/j.orggeochem.2005.03.011; https://doi.org/10.1016/j.orggeochem.2016.01.009). The ratio of pentacarboxylic acid to mellitic acid (B5CA/B6CA) has been used as an indicator of changes in fire regime (fire temperature). Note that arboreal pollen concentration and percentages and Quercus pollen percentages have been published under https://doi:10.5194/cp-10-643-2014, and can be found in this dataset in the form of raw data.